RESEARCH AND EDUCATION CENTER AS A MECHANISM FOR DEVELOPMENT OF THE UNIVERSITY - Boris E. Fishman (Высшее образование в России)
The article discusses the problem of integration of education and science, as embodied in the joint project, research, educational, organizational and methodological activities of the university educators. The article asserts that the local (at the level of faculties, departments, laboratories) communities, which are formed by educators may become the actors that ensure the overall development strategy of the university and vocational personal development of participants. The author characterizes the appropriate opportunities of the university scientific and educational centers. On the example of the scientific and educational center «Centre for Research and Innovation» of Sholom-Aleichem Priamursky State University there is represented a five-year experience of integrative activity based on actual multidisciplinary research. This allows to ensure training of highly qualified specialists, to develop and implement innovative educational programs. At the same time new stable collective subjects who are able to «get involved» in the process of overall development of the university have been forming.